How best to provide help to bereaved adolescents: a Delphi consensus study - Anna M Ross (BMC, 2021)
Abstract Background Many adolescents struggle with their grief and mental health issues after the death of a close person, such as a family member or a friend. Given the potentially devastating impact of the loss on the adolescent and their family, professional help can be warranted. However, little is known about how to best help these adolescents. This study aimed to address this gap by determining what help professionals (i.e., counselors) should provide to bereaved adolescents. Methods The Delphi method was used to achieve consensus regarding the importance of statements that describe actions a helping professional can take to help a bereaved adolescent. Statements were compiled through a systematic search of the scientific and grey literature, and reviewing interview data from a recent related research study with bereaved adolescents, parents and counselors. An expert panel (N = 49) comprising 16 adolescents, 14 parents and 19 helping professionals, rated each statement. Statements that were endorsed by at least 80% of panellists were considered consensus recommendations. Results Panellists endorsed 130 out of 190 statements as appropriate actions. These included help for a bereaved adolescent being offered on an ongoing basis, with support to be provided flexibly to meet individual adolescent needs and to acknowledge the agency of the adolescent. Support after a loss by suicide should be tailored to address specific suicide-related issues. Parents of bereaved adolescents should also be offered support so that they are better equipped to help their bereaved adolescent. Conclusions This study identified consensus recommendations on how a helping professional might best help bereaved adolescents. It is hoped that these recommendations will guide helping professionals and enhance adolescent grief interventions.